Problem Based Learning Model Assisted by Crossword Puzzles on the Learning Outcomes of Grade III Elementary School Pancasila Education Subjects Material Meaning of the Meaning of the Precepts of Pancasila - Azzahra, Astlanandita Fiska; Setiawan, Deni (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Learning, not referring to the Minister of Education, Culture, Research, and Technology Regulation Number 16 of 2022 concerning Process Standards, can result in low student learning outcomes. This study aims to analyse the effectiveness of the Problem-Based Learning model assisted by crossword puzzles on Pancasila Education learning outcomes on the meaning of the Pancasila principles in grade III. The research method used was an experiment with a quasi-experimental design. This study involved 40 grade III elementary school students. The research sample was selected using a purposive sampling method. Data was collected through tests, observations, interviews, and documentation. The data analysis technique used inferential statistics. The results of the analysis based on the results of the independent sample t-test showed that there was a significant difference between the post-test scores of the experimental class and the control class, with a significance value of 0.001. It was concluded that the problem-based learning model assisted by crossword puzzles effectively improved the learning outcomes of grade III elementary school students in the Pancasila Education subject on the meaning of the principles. The implication is that the application of a problem-based learning model assisted by crossword puzzles is efficacious in improving the learning outcomes of third-grade elementary school students on the material on the meaning of the Pancasila principles, so teachers are advised to use this method to strengthen the understanding of Pancasila values from an early age.